2005
DOI: 10.1103/physreva.72.043408
|View full text |Cite
|
Sign up to set email alerts
|

Avoided crossings in driven systems

Abstract: We characterize the avoided crossings in a two-parameter, time-periodic system which has been the basis for a wide variety of experiments. By studying these avoided crossings in the near-integrable regime, we are able to determine scaling laws for the dependence of their characteristic features on the non-integrability parameter. As an application of these results, the influence of avoided crossings on dynamical tunneling is described and applied to the recent realization of multiple-state tunneling in an expe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(53 reference statements)
3
12
0
Order By: Relevance
“…For example, we examined sharp avoided crossings between states localized in chaotic regions and those localized in integrable ones and demonstrated numerically the concomitant complete exchange of their Husimi structures. 34,38,57 We also showed that an avoided crossing between two mixed states tends to be broader than that between a predominately regular state and a predominately chaotic one. Furthermore, we found that the ␣-step size required to resolve an avoided crossing is correlated with the extent to which the participating states are localized in the chaotic and integrable portions of phase space.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…For example, we examined sharp avoided crossings between states localized in chaotic regions and those localized in integrable ones and demonstrated numerically the concomitant complete exchange of their Husimi structures. 34,38,57 We also showed that an avoided crossing between two mixed states tends to be broader than that between a predominately regular state and a predominately chaotic one. Furthermore, we found that the ␣-step size required to resolve an avoided crossing is correlated with the extent to which the participating states are localized in the chaotic and integrable portions of phase space.…”
Section: Discussionmentioning
confidence: 84%
“…This provides an example of a smooth exchange of character in a sharp avoided crossing, which has also been observed in other quantum chaotic systems. 38,57 The avoided crossings that we have observed between chaotic and regular states and between two chaotic states have all been sharp ones.…”
Section: -7mentioning
confidence: 93%
“…where the Floquet HamiltonianĤ F is a Hermitian operator in an extended Hilbert space which has time as a periodic coordinate [18,19,20]. Diagonalization ofĤ F in some appropriate basis in this space yields the Floquet eigenstates and eigenvalues.…”
Section: Stirap Transitions In the Quantum Pendulummentioning
confidence: 99%
“…(11) such that ǫ 0 c,qc , the Floquet eigenvalue in that zone corresponding to the physical state |χ c , is equal to ǫ 0 a,qa and the eigenvalue ǫ 0 b,q b is offset from this value by ∆. The degeneracy of these two eigenvalues and the near-degeneracy of the third requires that any perturbation analysis must be performed in the degenerate form [20]. Therefore, we expand the extended Hilbert space state |φ in powers of the small parameter λ |φ = |φ (0) + λ|φ (1) + λ 2 |φ (2) + .…”
Section: Stirap Transitions In the Quantum Pendulummentioning
confidence: 99%
“…[18,19]. For the driven square, two kinds of crossings, sharp and broad, were identified by Timberlake and Reichl [18].…”
Section: Diabatic Switching For Floquet Hamiltoniansmentioning
confidence: 99%